Designing and Standardizing two Dribbling Tests for the Initial selection of Individuals With Simple Mental Disabilities In Futsal - Sami, Firas; Shaker, Ali (Journal of Physical Education, 2018)
Designing and Standardizing two Dribbling Tests for the Initial selection of Individuals With Simple Mental Disabilities In FutsalFutsal for individuals with a simple mental disability has become very important in many sporting events. Therefore, the researcher considered that the basic skills tests should suite the level of the tested individuals in terms of their age and mental ability. The skill aspects were adopted as means for selecting players. The problem of research lies in designing and standardizing two tests of dribbling skills for this type of disability to be used for selection. The subjects were male simply mental disability aged 12 – 15, yet their mental age is 6 – 9 years from 12 institute as well as the Special Olympics. The data was collected and treated using proper statistical operations. The researchers concluded that dribbling tests were applied for the first time in Iraq thus can be used for selecting special Olympic futsal league and standardizing the results of the tests by placing criteria for evaluation. Finally the researchers recommended using these two tests for selection and evaluation.